A rapid access to addiction medicine clinic facilitates treatment of substance use disorder and reduces substance use - David Wiercigroch; Hasan Sheikh; Jennifer Hulme (BMC, 2020)
Abstract Background Substance use is prevalent in Canada, yet treatment is inaccessible. The Rapid Access to Addiction Medicine (RAAM) clinic opened at the University Health Network (UHN) in January 2018 as part of a larger network of addictions clinics in Toronto, Ontario, to enable timely, low barrier access to medical treatment for substance use disorder (SUD). Patients attend on a walk-in basis without requiring an appointment or referral. We describe the RAAM clinic model, including referral patterns, patient demographics and substance use patterns. Secondary outcomes include retention in treatment and changes in both self-reported and objective substance use. Methods The Electronic Medical Record at the clinic was reviewed for the first 26 weeks of the clinic's operation. We identified SUD diagnoses, referral source, medications prescribed, retention in care and self-reported substance use. Results The clinic saw 64 unique patients: 66% had alcohol use disorder (AUD), 39% had opiate use disorder (OUD) and 20% had stimulant use disorder. Fifty-five percent of patients were referred from primary care providers, 30% from the emergency department and 11% from withdrawal management services. Forty-two percent remained on-going patients, 23% were discharged to other care and 34% were lost to follow-up. Gabapentin (39%), naltrexone (39%), and acamprosate (15%) were most frequently prescribed for AUD. Patients with AUD reported a significant decrease in alcohol consumption at their most recent visit. Most patients (65%) with OUD were prescribed buprenorphine, and most patients with OUD (65%) had a negative urine screen at their most recent visit. Conclusion The RAAM model provides low-barrier, accessible outpatient care for patients with substance use disorder and facilitates the prescription of evidence-based pharmacotherapy for AUD and OUD. Patients referred by their primary care physician and the emergency department demonstrated a reduction in median alcohol consumption and high rates of opioid abstinence.